ДИСКУССИЯ "РЕАЛИЗМ-АНТИРЕАЛИЗМ" И ВОПРОС О СОСТОЯТЕЛЬНОСТИ ТЕОРИИ КОРРЕСПОНДЕНЦИИ В НЕОРЕАЛИСТИЧЕСКИХ КОНТЕКСТАХ - Лебедь, А. Е. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье исследуется понятие истины в контексте развития современной цивилизации. Определяются причины кризиса теории истины научного реализма. Анализируется сущность научного реализма в переходный период от корреспондентной теории истины к теории дефляционизма. Лебідь А. Є. Дискусія "Реалізм-Антиреалізм" і питання вмотивованості теорії кореспонденції в неореа-лістичних контекстах. У статті досліджується поняття істини в контексті розвитку сучасної цивілізації. Визначаються причини кризи теорії істини наукового реалізму. Аналізується сутність наукового реалізму в перехідний період від поняття кореспондентої теорії істини до теорії дефляціонізму. Ключові слова: істина, реалізм, науковий реалізм, антиреалізм. Lebed A. E. "Realism-antirealism" discussion and the problem of the theory of correspondence well-grounded in neorealist contexts. In the article the concept of truth in a context of development of a modern civilization is investigated. The reasons of crisis of science realism truth theory are defined. Its status in a transition period from correspondence theory of truth to deflationism is analyzed. Key words: truth, Realism, science Realism, Anti-Realism.